Information Support System for Socio-Economic Development Planning. (Part 3) Government and Administrative Information Systems: An Overview - Neelameghan, A. (Journal of Information and Knowledge, 1996)
Part 3 of this series on socio-economic development planning emphasizes that any development planning exercise must be supported by a whole range of information sources and systems apart from those mentioned in Parts 1 and 2. This Part mentions various government and administrative information systems necessary to support and ensure the effective and efficient performance of the different functions of a government in its efforts at development management. Of particular importance to a developing country is to enhance the capacity of its institutions and people to generate, capture, and circulate indigenous innovations and information as well as to evaluate technical know-how obtained from other countries as to its appropriateness and viability in the context of local development needs. Information systems are to be designed to support: Internal management functions; statutory functions; public services management functions; and policy making and planning functions. The subtypes of information under each of these categories are discussed.